Escritura, vida e constituição de si a arte do estilo - Olini, Polyana Cindia (2012)
The art of style takes from the body of the author his writing. It refers to the diversity of its internal states and, consequently, the possibility to express them verbatim. The writing is characterized by exceeding what is understood so far as language. The continuous variation present in the writing and style is what allows us to think philosophical projects and experiences as a formation of oneself, and therefore as constituting subjective and plural ways of cultivating and asserting one’s own life. This is called, in this work, the constitution of self, that is, an action that, through the writing and the elements that surround it, with all its banalities and its selfishness, is the constitutive power of the becoming what one is. As a result, this text develops these conceptual elements, experimenting with the theme of the constitution itself, pursuing the ideas of writing, (auto)biography, (self)formation, adopting the perspective of suspicion and deconstruction. Similarly, we approached the meeting with the life-death margin, the rupture of the distinction between philosophical and literary discourses, as well as the verbal and imagery speeches. In this context, examines and explains the meaning of gesture otobiographical as methodlabyrinth.